Addition and Subtraction of Integers with a Realistic Mathematics Education Approach - Mara Samin Lubis (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The aim of this research is to analyze the existing mathematics curriculum at the MIN Medan school and to identify how whole numbers are currently taught at the school. In addition to exploring and developing teaching strategies that incorporate real-world contexts for teaching integer addition and subtraction, to determine the effectiveness of the Realistic Mathematics Education approach in teaching integer addition and subtraction. The Realistic Mathematics Education (RME) Approach is one possible method. Through circumstances they can really experience, the RME technique offers pupils a learning opportunity to comprehend mathematical ideas. The learning process for adding and subtracting integers using the RME approach is described in this study using a qualitative descriptive methodology. Up to 30 pupils from class IIA served as research subjects for the study, which was carried out at MIN Medan. Data were gathered using observation notes and pictures. Data were gathered using observation notes and pictures. Data were reduced, displayed, and concluded, after which they were descriptively narrated. The results showed an effective learning process when the RME Approach was applied to the topic of addition and subtracting integers over the course of five meetings Keywords: Addition Subtraction Mathematic, Realistic Mathematics Education